Fungsi Sebab (F1) dan Fungsi Akibat (F2) dari Kemiskinan: Elaborasi Konseptual untuk Studi Kemiskinan Petani - Tarli Nugroho (Universitas Proklamasi 45 Yogyakarta, 2011)
Poverty eradication programmes so far did not work effectively because it cannot distinguish between the Fungsi Sebab (F1, Cause Function) with the Fungsi Akibat (F2, Result Function) from poverty. Poverty more responded according to the framework Fungsi Akibat (F2), so the causes of poverty not much cared for, and any attempt at tackling poverty in the end will always be charity. This article tries to assert the importance of proposing and the distinction between Fungsi Sebab (F1) and Fungsi Akibat (F2) to understand and explain the phenomenon of poverty, especially those occur among farmers.